Temporal and clonal characterization of neural stem cell niche recruitment in the medaka neuromast - Onistschenko, Jasmin; Kaminsky, Sabrina; Vázquez-Marín, Javier; Groß, Karen; Wang, Tianyu; Seleit, Ali; Dörr, Melanie; Centanin, Lázaro (Cells & development, 2023)
Stem cell populations are defined by their capacity to self-renew and to generate differentiated progeny. These unique characteristics largely depend on the stem cell micro-environment, the so-called stem cell niche. Niches were identified for most adult stem cells studied so far, but we know surprisingly little about how somatic stem cells and their niche come together during organ formation. Using the neuromasts of teleost fish, we have previously reported that neural stem cells recruit their niche from neighboring epithelial cells, which go through a morphological and molecular transformation. Here, we tackle quantitative, temporal, and clonal aspects of niche formation in neuromasts by using 4D imaging in transgenic lines, and lineage analysis in mosaic fish. We show that niche recruitment happens in a defined temporal window during the formation of neuromasts in medaka, and after that, the niche is enlarged mainly by the proliferation of niche cells. Niche recruitment is a non-clonal process that feeds from diverse epithelial cells that do not display a preferential position along the circumference of the forming neuromast. Additionally, we cover niche formation and expansion in zebrafish to show that distant species show common features during organogenesis in the lateral line system. Overall, our findings shed light on the process of niche formation, fundamental for the maintenance of stem cells not only in medaka but also in many other multicellular organisms.
Gesehen am 31.07.2023